The Palgrave Handbook of Presidents and Prime Ministers From Cleveland and Salisbury to Trump and Johnson
XIV, 495 p. 10 illus. in color.
Keywords: This handbook examines the personal relationships between American presidents and British prime ministers. It aims to determine how personal diplomacy shaped the Anglo-American relationship and whether individual leaders made the relationship “special.” From the great rapprochement of the 1890s to the Cold War and contemporary transatlantic rapport, the Anglo-American relationship has been one of global significance, making presidents and prime ministers central to international security, trade and commerce, culture, and communication. Naturally, it explores the ideas and convictions of presidents and prime ministers, the political parties they lead, as well as the political images constructed in the media and how the aura of the Anglo-American relationship might differ from the reality. With a deeper understanding of the leaders and the relationship they forge with their counterparts we come that much closer to appreciating the dynamics of transatlantic statecraft. .